CERT1 mutations perturb human development by disrupting sphingolipid homeostasis. - Gehin, C.; Lone, M.A.; Lee, W.; Capolupo, L.; Ho, S.; Adeyemi, A.M.; Gerkes, E.H.; Stegmann, A.P.; López-Martín, E.; Bermejo-Sánchez, E.; Martínez-Delgado, B.; Zweier, C.; et al. (Journal of Clinical Investigation, 2023)
Neural differentiation, synaptic transmission, and action potential propagation depend on membrane sphingolipids, whose metabolism is tightly regulated. Mutations in the ceramide transporter CERT (CERT1), which is involved in sphingolipid biosynthesis, are associated with intellectual disability, but the pathogenic mechanism remains obscure. Here, we characterize 31 individuals with de novo missense variants in CERT1. Several variants fall into a previously uncharacterized dimeric helical domain that enables CERT homeostatic inactivation, without which sphingolipid production goes unchecked. The clinical severity reflects the degree to which CERT autoregulation is disrupted, and inhibiting CERT pharmacologically corrects morphological and motor abnormalities in a Drosophila model of the disease, which we call ceramide transporter (CerTra) syndrome. These findings uncover a central role for CERT autoregulation in the control of sphingolipid biosynthetic flux, provide unexpected insight into the structural organization of CERT, and suggest a possible therapeutic approach for patients with CerTra syndrome.